The soft power of the Olympics in the age of Covid 19 - Rofe, J. S. (Olympic and Paralympic Analysis 2020: Mega events, media, and the politics of sport, 2021)
The Tokyo 2020 Summer Olympics Games was a Sport Mega Event (SME) like no other. The tensions evident in holding the world`s largest sporting event in one of the world`s most densely populated cities in the age of Covid raises pointed questions with respect to the values of hosting SME`s. Jules Boykoff`s NOlympians ably demonstrates historical and contemporary opposition to Olympic hosting. Nonetheless, the benefits of hosting SME`s - promoted by the International Olympic Committee and other governing bodies in sport - are often considered in terms of the perceived soft power benefits that accrue to the hosts. Soft power - the power of attraction and trust in relations amongst different polities, is a much debated term, but one that has proved remarkably durable since it was first coined by scholar Joseph Nye Jr in the early 1990s. Supposed soft power benefits have been typically measured in terms of visitor numbers to a city, hotel beds filled, cultural exchange events, and tickets sold to the games themselves, alongside increased GDP - a harder power measure. Covid corrupted these criteria. The impact on the athletes and administrators was huge - medals were ultimately won and lost on the basis of what the impact a year`s delay meant to athletic performance. Similarly, the impact on the hosts affords an opportunity to reappraise a soft power typography for hosting SMEs away from previous attempts to classify soft power success in terms of physical footfall - tickets sales et al. The soft power impact of Tokyo 2020 needs to be considered in its own right.